KEMAMPUAN BERPIKIR ALJABAR SISWA SEKOLAH PENDIDIKAN DASAR KELAS V DAN KELAS VII: CROSS-SECTIONAL STUDY - Dian Permatasari; Idris Harta (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2018)
The study aimed to describe 1) students’ algebraic thinking ability of elementary school grade V, 2) students’ algebraic thinking ability of junior high school grade VII, and 3) the development of students’ algebraic thinking ability from elementary school kelas V to junior high school grade VII. This study was a cross-sectional design with quantitive descriptive approach. The subjects of this study were 77 students of elementary school grade V and 95 students of junior high school grade VII. The sampling technique method used was stratified purposive sampling techniques and of analysis techniques with a descriptive analysis. The instrument used were algebraic thinking problems that consist of 3 components, namely, generational, transformational, and global meta-level activity. The results showed that 1) the students’ algebraic thinking ability of elementary school grade V was in the medium criteria; 2) the students’ algebraic thinking ability of junior high school grade VII was in medium criteria; 3) the average of gain score of students in junior high school grade VII was higher than students in elementary school grade V and students in elementary school grade V because lementary school students grade V until junior high school grade VII undergo a transition of thinking processes from arithmetic thinking to algebra thinking gradually, from simple cases to more complex cases. Generally, students of grade V and VII have moderate algebraic thinking skills. However, the ability of students of grade VII is higher than students of grade V because they have formally obtained algebra material. AbstrakPenelitian ini bertujuan untuk mendeskripsikan 1) kemampuan berpikir aljabar siswa Sekolah Dasar kelas V, 2) kemampuan berpikir aljabar siswa Sekolah Menengah Pertama kelas VII, dan 3) perkembangan kemampuan berpikir aljabar siswa dari sekolah dasar hingga sekolah menengah. Penelitian ini merupakan penelitian cross-sectional dengan pendekatan deskriptif kuantitatif. Subjek penelitian ini 77 siswa SD kelas V dan 95 siswa SMP kelas VII. Penentuan subjek penelitian dilakukan dengan teknik stratified purposive sampling dengan teknik analisis deskriptif. Instrumen yang digunakan berupa tes kemampuan berpikir aljabar yang memuat 3 komponen kegiatan yaitu kegiatan generasional, transformasional, dan global meta-level. Hasil penelitian menunjukkan bahwa: 1) kemampuan berpikir aljabar siswa SD kelas V berada dalam kriteria sedang; 2) kemampuan berpikir aljabar siswa SMP kelas VII berada dalam kriteria sedang; 3) rata-rata kemampuan siswa SMP kelas VII lebih tinggi dibanding rata-rata siswa SD kelas V karena siswa SD kelas V sampai dengan SMP kelas VII mengalami suatu transisi proses berpikir dari berpikir aritmatika menuju berpikir aljabar secara bertahap, mulai dari kasus sederhana sampai dengan kasus yang lebih kompleks. Kesimpulan, siswa kelas V dan kelas VII rata-rata memiliki kemampuan berpikir aljabar sedang. Namun, kemampuan siswa kelas VII lebih tinggi daripada siswa kelas V karena siswa Kelas VII telah memperoleh materi aljabar secara formal.